Evaluation of the Performance of AmpliSeq and SureSelect Exome Sequencing Libraries for Ion Proton - Gampawar, Piyush; Saba, Yasaman; Werner, Ulrike; Schmidt, Reinhold; Müller-Myhsok, Bertram; Schmidt, Helena (Frontiers in Genetics, 2019)
Library preparation for whole exome sequencing is a critical step serving the enrichment of the regions of interest. For Ion Proton, there are only two exome library preparation methods available, AmpliSeq and SureSelect. Although of major interest, a comparison of the two methods is hitherto missing in the literature. Here we systematically evaluate the performance of AmpliSeq and SureSelect and present an improved variant calling pipeline. We used 12 in-house DNA samples with genome-wide and exome microarray data and a commercially available reference DNA (NA12878) for evaluation. Both methods had a high concordance (>97%) with microarray genotypes and when validating against NA12878 a sensitivity and positive predictive value (PPV) of >93% and >80%, respectively. Application of our variant calling pipeline decreased the number of false positive variants dramatically by 90% and resulted in PPV of 97%. This improvement is highly relevant in research as well as clinical setting.